Social determinants of intra-urban differentials of admissions by respiratory diseases in Salvador (BA), Brazil - Fernanda Pedro Antunes; Maria da Conceição Nascimento Costa; Jairnilson Silva Paim; Álvaro Cruz; Ligia Maria Vieira da Silva; Mauricio Barreto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: Respiratory diseases (RD) represent a significant cause of hospitalization in Brazil, occupying the first position in the rank by group of diseases. OBJECTIVE: To identify social determinants (SD) of intra-urban differentials of hospitalizations by RD and their main types (asthma and pneumonia) a study of spatial aggregation was carried out in Salvador (BA), between 2001 and 2007, taking Information Zones (IZ) as unit of analysis. METHODS: Data on hospitalizations were provided by the Health Department of Bahia State. Socioeconomic indicators were obtained from the Demographic Census carried out in 2000, and the number of health centers was acquired from the National Register of Health Services. RESULTS: Multiple linear regression analysis indicated association between spatial variation of the rates of hospitalization due to RD and income (β = 0.54, p < 0.001) and rate of health facilities per 10,000 inhabitants (β = 2.91, p < 0.001). Crowding was not associated. CONCLUSION: The identification of variation in SD in hospitalizations by RD in the IZ of Salvador will help in the decision-making process by public managers in defining goals and effective measures to reduce inequities in health.